Influence of Mahayana-Vajrayana School on the Sacred Characteristics of Theravada Vihara in Indonesia - Rahadhian Prajudi Herwindo; Singgih Salim (UIN Sunan Gunung Djati Bandung, 2022)
After Buddha parinibbana, difference of views between his disciples in interpreting Dhamma result in the creation of three main Buddhist schools: Theravada, Mahayana, and Vajrayana. With slightly different philosophies, these schools also have their own unique architectural characteristics to represent sacredness. However, due to the absence of any architectural literature, wide interpretations of Buddhist teachings, and acculturation with local culture, sacred characteristics of Buddhist architecture became mixed and difficult to distinguish. This research aims to study the influence of Mahayana and Vajrayana schools on the sacred characteristics of Theravada Buddhist architecture in Indonesia. Elaboration of Buddhist architecture and sacredness theory are used to analyse case study in surrounding environment, figure, mass structure, spatial planning, and ornamentation scope to obtain comprehensive acculturation picture of Mahayana and Vajrayana philosophy on Theravada vihara in Indonesia. Based on the results of the analysis, it can be seen that the circular shape that was characteristic of the early Theravada school in the architectural form of the monastery began to be abandoned and the use of anthropomorphic Buddha and iconic symbols as ornamentation elements which were only known in the development of Mahayana and Vajrayana schools.